Mothers and Divorce : Legal, Economic, and Social Dilemmas. - Arendell, Terry (University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1986.
Description based upon print version of record.
Keywords: Divorced mothers -- United States -- Social conditions.; Divorced mothers -- United States -- Economic conditions.; Divorced mothers -- Legal status, laws, etc. -- United States.; Divorce -- Law and legislation -- United States.; Marital property -- United States.; Divorce.; Biens matrimoniaux -- États-Unis.; Divorce; Divorce -- Law and legislation; Divorced mothers -- Economic conditions; Divorced mothers -- Legal status, laws, etc.; Divorced mothers -- Social conditions; Marital property; United States